A Structural Model of the Influence of Immigrant Mothers' Depressive Symptoms and Home Environment on Their Children's Early Developmental Outcomes in Taiwan. Issue 6 (8th October 2013) - Chen, Hung‐Hui; Hwang, Fang‐Ming; Wang, Kung‐Liahng; Chen, Chwen‐Jen; Lai, Jerry Cheng‐Yen; Chien, Li‐Yin
Abstract In this cross‐sectional study of 61 immigrant mothers and their 6‐ to 24‐month‐old children in Taiwan, we examined the structure of relationships among maternal depressive symptoms, quality of the child‐rearing home environment, and child development using a partial least squares approach. Maternal depressive symptoms as measured by the Edinburgh Postnatal Depression Scale had a direct and negative effect on the quality of the home environment as measured by the IT‐HOME, which in turn had a direct and positive effect on child development as measured by the Comprehensive Developmental Inventory for Infants and Toddlers. Maternal depressive symptoms did not directly affect child development, suggesting that the quality of the home environment mediated the relationship between maternal depressive symptoms and child development. © 2013 Wiley Periodicals, Inc. Res Nurs Health 36: 603–611, 2013